Prolactin Inducible Protein, but Not Prolactin, Is Present in Human Tears, Is Involved in Tear Film Quality, and Influences Evaporative Dry Eye Disease - Jüngert, Katharina; Paulsen, Friedrich; Jacobi, Christina; Horwath-Winter, Jutta; Garreis, Fabian (Frontiers in Medicine, 2022)
Decreased production of the aqueous component of the tear film is an important cause of the development of dry eye disease (DED). Tear production is influenced by hormones and hormone-like factors. Prolactin (PLR), a multifunctional pituitary gland hormone, is regularly present in tears of small laboratory animals. In humans, serum PLR concentration correlates with tear quality. To gain deeper insights of the possible effects of PRL, prolactin receptor (PRLR) and prolactin inducible protein (PIP), we analyzed the three proteins in the human lacrimal apparatus and in tears of healthy volunteers as well as patients suffering from DED. Expression of PRL, PRLR and PIP analyzed in the human lacrimal apparatus obtained from cadavers as well as cell lines by RT-PCR and immunohistochemistry. In addition, tears from DED patients and healthy volunteers analyzed by ELISA to determine the concentration of PRL and PIP. RT-PCR analyses revealed gene expression of PRLR and PIP in human tissue samples of cornea, lacrimal glands, and eyelids, whereas only PIP, but not PRLR, was detectable in immortalized corneal epithelial cells. Immunohistochemistry revealed for the first time the expression and localization of PRL, PRLR, and PIP in human tissues of the lacrimal apparatus and at the ocular surface. PRL and PRLR were detectable in corneal epithelium, lacrimal glands, and Meibomian glands. Tears from DED patients revealed significantly increased PIP concentrations, whereas PRL was undetectable in tears of DED patients and healthy volunteers. PRL, PRLR, and PIP are found in the lacrimal apparatus and on the ocular surface. PIP, but not PRL, is present in human tears and appears to be involved in the physiology of tear film quality. PIP may affect tear quality in two different ways: (1) the amount of the aqueous component of tears by interacting with aquaporin 5 in the lacrimal gland and (2) evaporative DED through immunomodulatory effects. Further functional analyses are needed to fully elucidate the effects of PRL and PIP-associated factors in the connection of DED.